2019
DOI: 10.2139/ssrn.3590902
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of Natural Disasters on Households and Small Businesses in India

Abstract: The views expressed in this publication are those of the authors and do not necessarily reflect the views and policies of the Asian Development Bank (ADB) or its Board of Governors or the governments they represent.ADB does not guarantee the accuracy of the data included in this publication and accepts no responsibility for any consequence of their use. The mention of specific companies or products of manufacturers does not imply that they are endorsed or recommended by ADB in preference to others of a similar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Recent studies by Bisht et al 2018;Dash et al 2009;Deshpande et al 2016;Dubey and Sharma 2018;Goswami et al 2006;Guhathakurta et al 2011;Jain et al 2017;Krishnamurthy et al 2009 reported a significant increase in extreme precipitation events on a national and regional scale. Flooding is becoming more common in India as extreme weather events become more common, accounting for half of all natural disasters (Patankar 2020). According to flood statistics from the Government of India, the flood-affected area in India has increased from 25 million hectares (Mha) in 1952 to 40 Mha in 1980 and 49.8 Mha in 2011 (Bhanduri 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies by Bisht et al 2018;Dash et al 2009;Deshpande et al 2016;Dubey and Sharma 2018;Goswami et al 2006;Guhathakurta et al 2011;Jain et al 2017;Krishnamurthy et al 2009 reported a significant increase in extreme precipitation events on a national and regional scale. Flooding is becoming more common in India as extreme weather events become more common, accounting for half of all natural disasters (Patankar 2020). According to flood statistics from the Government of India, the flood-affected area in India has increased from 25 million hectares (Mha) in 1952 to 40 Mha in 1980 and 49.8 Mha in 2011 (Bhanduri 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Extreme ood events in uence around 21 million people globally, which may rise to 54 million by 2030 due to climate change and socioeconomic growth (Luo et al, 2015). According to Patankar (2019), 278 ood events occurred between 1980 and 2017 in India, which caused a loss of 58.7 billion USD and affected 750 million people. Gangopadhyay et al (2018) reported that ood causes around USD 7500 million in economic losses annually in India.…”
Section: Introductionmentioning
confidence: 99%